Bisnis Lansia Berbasis Syariah: Studi Kemandirian Desa Melalui Usaha Sabun, Bawang Goreng, dan Keripik Talas di Desa Sait Buttu - Farhan Fadilah Akbar; Bintang Andira Febrianti; Agil Alwi Gegoh; Asma Ardi Ilham; Atiya Atiya; Farhan Tri Alrihsan farhan (Getpress Management Journals, 2025)
Village independence is one of the goals of sustainable development that focuses on empowering local communities. The elderly are often perceived merely as beneficiaries, whereas in fact, they possess economic potential that can be further developed. This article discusses a community service program in Sait Buttu Village with a sharia-based business approach that involves the elderly in soap production, fried shallots, and taro chips enterprises. The method applied was a participatory approach through training, mentoring, and the implementation of Islamic economic law principles. The results of the program indicate an increase in elderly productivity, the strengthening of family economies, and contributions to village independence. Furthermore, this initiative has proven to be in line with sharia principles, namely halal, thayyib (wholesome), fair, and beneficial for the community.